Ruminal degradation and estimated energy and protein values for ruminants of Durum wheat varieties grown in three locations. Issue 5 (9th May 2020) - Krieg, Jochen; Titze, Natascha; Steingass, Herbert; Friedrich H. Longin, C.; Rodehutscord, Markus
Abstract: Durum wheat is mainly used in pasta production, but may also be used as animal feed, for example as concentrate for dairy cows. Data on the ruminal degradation of Durum grains are scarce. Hence, the objective of the present study was to describe ruminal in situ crude protein (CP) and starch (ST) degradation, to investigate in vitro gas production kinetics, and to estimate utilisable CP at the duodenum (uCP) in vitro of five Durum varieties from three growing locations. Metabolisable energy (ME) and digestibility of organic matter (dOM) were also estimated using in vitro data. In situ incubations were conducted in three lactating j ersey cows over defined timespans from 1 to 72 hr. Ruminal degradation parameters were estimated using exponential regression, and effective ruminal degradation was predicted for a ruminal passage rate of 8%/hr (ED8 ). In situ CP ( a = 11%–19%; b = 80%–88%; c = 23%–33%/hr) and ST ( a = 22%–39%; b = 60%–78%; c = 61%–123%/hr) degradation kinetics varied among samples and were influenced by location. Some samples showed a remarkably high ST degradation rate of up to 123%/h, which can significantly influence rumen pH and health when high amounts are incorporated into dairy rations. However, the ED of CP (77%–82%) and ST (91%–95%), and the in vitro estimates of ME (13.6–14.1 MJ/kg DM), dOM (92%–96%), and uCP (183–195 k/g DM) varied within a relatively small range. Hence, it may be adequate to use the mean values of these Durum grain characteristics when rations for ruminants are calculated and a differentiation depending on variety and location may not be necessary.